2017
DOI: 10.1038/s41593-017-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of developing myelin sheath elongation by oligodendrocyte calcium transients in vivo

Abstract: How action potentials regulate myelination by oligodendrocytes is uncertain. We show that neuronal activity raises [Ca] in developing oligodendrocytes in vivo and that myelin sheath elongation is promoted by a high frequency of [Ca] transients and prevented by [Ca] buffering. Sheath elongation occurs ~1 h after [Ca] elevation. Sheath shortening is associated with a low frequency of [Ca] transients but with longer duration [Ca] bursts. Thus, [Ca] controls myelin sheath development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
180
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(195 citation statements)
references
References 27 publications
13
180
0
Order By: Relevance
“…There are a number of signals that could be modified by iTBS to increase internode length. For example, GABAergic signaling in neocortical slices, cultured from P8 mice, is associated with increased internode length (Hamilton et al, ), however, iTBS also increased internode length in the CC, suggesting that longer internodes may instead result from increased glutamate‐induced calcium signaling in the developing myelin sheaths (Baraban, Koudelka, & Lyons, ; Krasnow, Ford, Valdivia, Wilson, & Attwell, ). While iTBS could lengthen internodes by modulating neurons, the alternative is that it has a direct effect on the extending internodes of maturing oligodendrocytes, perhaps influencing local calcium signaling (Grehl et al, ), and further research is required to dissect the primary and secondary effects of iTBS on these cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of signals that could be modified by iTBS to increase internode length. For example, GABAergic signaling in neocortical slices, cultured from P8 mice, is associated with increased internode length (Hamilton et al, ), however, iTBS also increased internode length in the CC, suggesting that longer internodes may instead result from increased glutamate‐induced calcium signaling in the developing myelin sheaths (Baraban, Koudelka, & Lyons, ; Krasnow, Ford, Valdivia, Wilson, & Attwell, ). While iTBS could lengthen internodes by modulating neurons, the alternative is that it has a direct effect on the extending internodes of maturing oligodendrocytes, perhaps influencing local calcium signaling (Grehl et al, ), and further research is required to dissect the primary and secondary effects of iTBS on these cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that glutamate released by axons is sensed by AMPA receptors on oligodendrocyte precursor (NG2) cells, which influences their proliferation and differentiation [17,19,32,[64][65][66]. There is also firm evidence that glutamate derived from active axons is sensed by AMPA and NMDA receptors expressed on the surrounding myelin sheath, resulting in calcium signals proposed to play a central role in coupling axonal activity and integrity with oligodendrocyte metabolism and driving formation of myelin [67][68][69][70][71][72]. Metabolic support of axons was moreover suggested to be provided by astrocytes, which break down glycogen and release lactate into the extracellular space that can then be taken up by axons during periods of high energy demand [73,74].…”
Section: Relevance Of Different Sodium Influx Pathwaysmentioning
confidence: 99%
“…Indeed, agonist‐evoked [Ca 2+ ] i oscillations are a characteristic property of cells expressing some receptors, including AMPA receptors, and represent a signaling system that regulates numerous processes in all cell types including proliferation and cellular differentiation (Dolmetsch et al , ). Recently, Krasnow et al () provide evidence that calcium transients in developing oligodendrocytes, including those evoked by neuronal activity, drive myelin sheath elongation presumably controlling proteins regulating cytoskeletal growth and myelin assembly. In this context, and in line with our findings showing the relevant contribution of NCX3 to D‐Asp‐evoked [Ca 2+ ] i oscillations in OPC, a very recent study demonstrated that NCX‐mediated Ca 2+ influx is required for sustaining spontaneous [Ca 2+ ] i oscillations occurring in differentiating oligodendrocytes at DIV4‐5 in cultures (Hammann et al , ).…”
Section: Discussionmentioning
confidence: 99%